2023
DOI: 10.1002/jmri.28589
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Diffusion Coefficient as Imaging Biomarker for Identifying IDH Mutation, 1p19q Codeletion, and MGMT Promoter Methylation Status in Patients With Glioma

Abstract: Background Glioma genotypes are of importance for clinical decision‐making. This data can only be acquired through histopathological analysis based on resection or biopsy. Consequently, there is a need for alternative biomarkers that noninvasively provide reliable information for preoperatively identifying molecular characteristics. Purpose To investigate apparent diffusion coefficient (ADC) as imaging biomarker for preoperatively identifying glioma genotypes based on the 2021 World Health Organization (WHO) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
3
3
0
Order By: Relevance
“…It highlights the relationship between cellular density and water diffusion in gliomas, with aggressive tumors showing lower ADC values due to high cellular density restricting water diffusion, and less aggressive tumors exhibiting higher ADC values. 27 Our study confirms that ADC radiomics significantly improves IDH-wt and IDH-mut non-codel glioma prediction, a finding consistent with previous research indicating that IDH-mut gliomas show higher ADC values compared to IDH wt 28 and texture features of ADC are useful for determining the 1p/19q status. 28–30 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It highlights the relationship between cellular density and water diffusion in gliomas, with aggressive tumors showing lower ADC values due to high cellular density restricting water diffusion, and less aggressive tumors exhibiting higher ADC values. 27 Our study confirms that ADC radiomics significantly improves IDH-wt and IDH-mut non-codel glioma prediction, a finding consistent with previous research indicating that IDH-mut gliomas show higher ADC values compared to IDH wt 28 and texture features of ADC are useful for determining the 1p/19q status. 28–30 …”
Section: Discussionsupporting
confidence: 89%
“… 27 Our study confirms that ADC radiomics significantly improves IDH-wt and IDH-mut non-codel glioma prediction, a finding consistent with previous research indicating that IDH-mut gliomas show higher ADC values compared to IDH wt 28 and texture features of ADC are useful for determining the 1p/19q status. 28–30 …”
Section: Discussionsupporting
confidence: 89%
“…Among IDH mutant gliomas, 1p/19q intact gliomas seem to exhibit higher ADC values than 1p/19q codeleted gliomas. In contrast to our study, this analysis was not based on a fully automated extraction of imaging metrics from all tumor volumes but on individually placed regions of interest, which poses a possible source of error [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al investigated apparent diffusion coefficient ratio (ADC ratio ) value as a preoperative diagnostic imaging biomarker in gliomas and concluded that ADC ratio values enable the identification of 1p/19q co‐deletion and IDH mutation status in IDH mutated glioma. In the design of the present study by Ma et al, there are IDH mutant/1p19q mutant, IDH mutant/1p19q intact, and IDH wild‐type groups, and also in high‐grade glioma, O(6)‐methylguanine‐DNA methyltransferase (MGMT) methylated and non‐methylated groups 8 . MGMT methylation was not examined in the low‐grade gliomas, which is not unreasonable as the clinical impact of MGMT status on benefit from temozolomide or other alkylating agents has not been determined.…”
mentioning
confidence: 84%
“…In the design of the present study by Ma et al, there are IDH mutant/1p19q mutant, IDH mutant/1p19q intact, and IDH wild-type groups, and also in high-grade glioma, O(6)-methylguanine-DNA methyltransferase (MGMT) methylated and non-methylated groups. 8 MGMT methylation was not examined in the lowgrade gliomas, which is not unreasonable as the clinical impact of MGMT status on benefit from temozolomide or other alkylating agents has not been determined. Furthermore, MGMT methylation in low-grade gliomas is often significantly associated with IDH mutation and/or 1p/19q co-deletion and these are well-established prognostic factors for survival.…”
mentioning
confidence: 99%